2004
DOI: 10.1142/s0217979204025464
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Adaptation in Large Population Games

Abstract: We consider a version of large population games whose players compete for resources using strategies with adaptable preferences. The system efficiency is measured by the variance of the decisions. In the regime where the system can be plagued by the maladaptive behavior of the players, we find that diversity among the players improves the system efficiency, though it slows the convergence to the steady state. Diversity causes a mild spread of resources at the transient state, but reduces the uneven distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…5) By introducing diversity to the preference of policies of the agents, we have recently demonstrated that a better system efficiency can be attained. 6) Since agent cooperation is important in this regime, it would be interesting to study the mechanisms by which they adapt mutually, and their effects on the system efficiency.…”
Section: §1 Introductionmentioning
confidence: 99%
“…5) By introducing diversity to the preference of policies of the agents, we have recently demonstrated that a better system efficiency can be attained. 6) Since agent cooperation is important in this regime, it would be interesting to study the mechanisms by which they adapt mutually, and their effects on the system efficiency.…”
Section: §1 Introductionmentioning
confidence: 99%